2019
DOI: 10.1097/rli.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Using a Dual-Input Convolutional Neural Network for Automated Detection of Pediatric Supracondylar Fracture on Conventional Radiography

Abstract: Objectives This study aimed to develop a dual-input convolutional neural network (CNN)–based deep-learning algorithm that utilizes both anteroposterior (AP) and lateral elbow radiographs for the automated detection of pediatric supracondylar fracture in conventional radiography, and assess its feasibility and diagnostic performance. Materials and Methods To develop the deep-learning model, 1266 pairs of AP and lateral elbow radiographs examined between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 26 publications
0
59
0
Order By: Relevance
“…They have successfully been used for fracture detection and localization on radiographs [3][4][5][6][7][8][9][10][11][12]. Training data for automated fracture detection have been heterogeneously labeled by orthopedic surgeons [5], orthopedic specialists [6], radiology [10,11,13,14] or orthopedic [15] residents and general radiologists [4] or specialized musculoskeletal radiologists [7,8]. Cheng et al [8] used registry data to label hip fractures on radiographs and only Olczak et al [12] used key phrases of radiology reports to label radiographs for the training set.…”
Section: Introductionmentioning
confidence: 99%
“…They have successfully been used for fracture detection and localization on radiographs [3][4][5][6][7][8][9][10][11][12]. Training data for automated fracture detection have been heterogeneously labeled by orthopedic surgeons [5], orthopedic specialists [6], radiology [10,11,13,14] or orthopedic [15] residents and general radiologists [4] or specialized musculoskeletal radiologists [7,8]. Cheng et al [8] used registry data to label hip fractures on radiographs and only Olczak et al [12] used key phrases of radiology reports to label radiographs for the training set.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies 6 , 24 , 25 reported the area under the receiving operating characteristics curve (AUC-ROC) to evaluate IV and EV performance. The AUC is a common metric to report CNN performance, 26 where a value of 1.0 indicates perfect discriminatory performance, whereas 0.5 indicates a prediction equal to that of chance.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Zhou et al 27 addressed both fracture detection and classification. The CNNs detected fractures on a single anatomical location like the wrist, 6 , 24 elbow, 25 or ribs. 27 Input features of three studies 6 , 24 , 25 were conventional radiographs; one study used CT scans.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interdisciplinary research group started working in the field of pediatric trauma computer vision applications in 2018 [52]. As described [90,91], AI can be helpful in the domain of automated fracture detection. One of the main hurdles in establishing AI algorithms is the lack of annotated training data sets and data quality.…”
Section: Personal Experiencesmentioning
confidence: 99%